Analysis of Decision of The Honorary Council of The Constitutional Court Number 2/MKMK/L/11/2023 Based on The Constitutional Court Regulation Number 1 of 2023 Concerning the Honorary Council of The Constitutional Court - Tuanany, Egfa G; Siti Barora Sinay; Andika Adhyaksa (Candela Edutech Indonesia, 2025)
The Constitutional Court's Honorary Council's decision was deemed wrong in imposing sanctions on the Chief Justice of the Constitutional Court, Anwar Usman. This study aims to determine how the implementation of the Constitutional Court Regulation of the Republic of Indonesia Number 1 of 2023 concerning the Honorary Council of the Constitutional Court is carried out against the Decision of the Honorary Council of the Constitutional Court Number 2/MKMK/L/11/2023 and to find out and understand what is the basis for consideration for the judges of the Honorary Council of the Constitutional Court in the decision Number 2/MKMK/L/11/2023. The type of research used in this study is normative legal research, using a research approach by examining and reviewing the object of research through laws and regulations by sharpening research data that aims to find out the problems being discussed, while the type of research is qualitative using descriptive analysis. The results of the study indicate that the Honorary Council of the Constitutional Court did not apply the Constitutional Court Regulation Number 1 of 2023 concerning the Honorary Council of the Constitutional Court as it should so that in the decision of the MKMK Number 2/MKMK/L/11/2023 it cannot provide legal certainty. Therefore, the provisions governing the types of sanctions for reported judges who are proven to have committed ethical violations are not explained properly. However, the decision is final and binding internally on the Constitutional Court.